2017
DOI: 10.1002/2017gl072867
|View full text |Cite
|
Sign up to set email alerts
|

Global bounds on nitrogen gas emissions from humid tropical forests

Abstract: Denitrification and hydrologic leaching are the two major pathways by which nitrogen (N) is lost from the terrestrial biosphere. Humid tropical forests are thought to dominate denitrification losses from unmanaged lands globally, but there is large uncertainty about the range and key drivers of total N gas emissions across the biome. We combined pantropical measures of small watershed stream chemistry with ecosystem modeling to determine total N gas losses and associated uncertainty across humid tropical fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…, Brookshire et al. ). Others have shown that terrestrial denitrification fluxes are underestimated by up to 98%, and that N gaseous export exceeds NO 3 − by a factor six (Fang et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Brookshire et al. ). Others have shown that terrestrial denitrification fluxes are underestimated by up to 98%, and that N gaseous export exceeds NO 3 − by a factor six (Fang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical estimations of N 2 production from old tropical forests were roughly four times higher than N 2 O production (Hedin et al 2003), and up to five times in process-based models (Bai and Houlton 2009). Moreover, recent isotopic studies and ecosystem models have pointed out that denitrification losses in humid tropical forests make up a large fraction of total ecosystem N losses (Houlton et al 2006, Brookshire et al 2017. Others have shown that terrestrial denitrification fluxes are underestimated by up to 98%, and that N gaseous export exceeds NO 3 À by a factor six (Fang et al 2015).…”
Section: Nitrogen Budget For African Tropical Forestsmentioning
confidence: 99%
See 2 more Smart Citations
“…, Brookshire et al. ), emission rates also vary widely by up to two orders of magnitude among sites, from 0.1 to > 9 kg N 2 O‐N ha −1 yr −1 , with a reported mean of 2.8 kg N 2 O‐N ha −1 yr −1 (Erickson et al. , Castaldi et al.…”
Section: Discussionmentioning
confidence: 99%